CLINICAL ASPECTS OF COMPLEX ORAL REHABILITATION IN PATIENTS WITH DYSFUNCTIONAL SYNDROME OF THE STOMATOGNAT SYSTEM AND ITS INTERFERENCES WITH SCHIZOPHRENIA - Part 1 - Lucian Stefan Burlea; Ana Maria Ciubara; Veronica Serban Pintiliciuc; Tudor Hamburda; Ovidiu Stamatin; Liana Aminov; Bogdan Constantin Mihaila; Doriana Agop Forna; Toma Marius Cristian; Laura Elisabeta Checherita (Romanian Society of Oral Rehabilitation, 2024)
Dysfunctional syndrome of the stomatognathic system interferes with interferes with many pathologies among which in the present situation, with the characteristics of complex psychiatric pathology. There are cases with a high index of complexity that can be treated only by interdisciplinary approach dentistry-psychiatry. Complex oral rehabilitation imposes strategies and treatments to facilitate a good result in increasing the quality of life and the optimum result of patients with schizophrenia-type psychiatric elements.